Changes in the phosphorylation of claudins during the course of experimental colitis - Li, Jing (Int J Clin Exp Pathol, 2015)
The phosphorylation of the tight-junction protein claudin causes allosterism, endocytosis and changes in the polarity of the epithelium, thus affecting the barrier function. The phosphorylation status of claudin during the course of colitis has not been demonstrated. In the present study, we found that the phosphorylated claudin-4 and claudin-7 contents were increased in experimental colitis at days 6 and 8, and colonic phosphorylated claudin-6 was found to be increased at day 4 and day 8. Colonic phosphorylated claudin-5 was found to be decreased at day 4 but increased at day 6. These changes were accompanied by increases in intestinal permeability. In T84 cells, phosphorylated claudin-3 was increased at 48 h but decreased at 72 h after lipopolysaccharide (LPS) treatment. Phosphorylated claudin-5 and claudin-7 were decreased 72 h after LPS treatment, while phosphorylated claudin-6 was increased at 72 h after LPS treatment. We conclude that the phosphorylation of colonic claudins was changed during the course of colitis, which may be related to the change in the intestinal barrier function. Cytokine such as LPS was found to affect the phosphorylation of colonic claudins.